Use of the Thunkable Platform in Preparing a Digital Arabic-Indonesian Dictionary as a Learning Resource for Arabic Language Learners - Khoiri, Khabibul; Umam, Lukman Habibul; Mustofa, Yusuf; Puspitasari, Ema (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to answer the anxiety that current Arabic language learners must immediately respond to the increasingly massive development of digital technology by presenting a thunkable platform in creating a digital Arabic-Indonesian dictionary application as an independent learning resource for Arabic language learners. With the millennial generation preferring digital over printed resources, this research explores using the Thunkable platform to create a digital Arabic-Indonesian dictionary as a self-learning tool. Using a waterfall and qualitative descriptive approach, the study outlines the creation and use of the app. The data in this research are data on developing a digital Arabic-Indonesian dictionary via a thunkable platform, application user data, data on using digital dictionary features, and evaluation data on Arabic language learning using a digital dictionary. The data collection technique this research uses involves qualitative methods, providing a comprehensive overview of how the Thunkable platform can develop digital dictionaries for Arabic language learning. Meanwhile, the data sources in this research were obtained from observations, interviews, questionnaires, learning tests, application log analysis, and documentation studies, which will produce in-depth data regarding the effectiveness and efficiency of the application as a learning resource for Arabic language learners. Then, the data obtained was analyzed in several stages: data collection, data reduction, data presentation, and drawing conclusions. Thanks to its translator feature and block-based programming, thunkable simplifies the process by eliminating the need for time-consuming vocabulary inventories and manual coding. The digital dictionary also works offline, offering flexible access for learners anytime, anywhere. This study demonstrates how technology can support independent learning and enhance Arabic language skills.